Severinia buxifolia Leaves: Isolation, Characterization of Major Metabolites from the Bioactive Fractions and their Antiprotozoal Activity - Nour, Safaa; Salama, Maha; Mahrous, Engy; El-Askary, Hesham; Hifnawy, Mohamed; Abdel Kawy, Mustafa A. (Jordan Journal of Pharmaceutical Sciences, 2023)
In an effort to explore herbal drugs as treatment for some neglected tropical diseases (NTDs), Severinia buxifolia (Poir) Ten, was selected and investigated for its antiprotozoal activity. Based on this objective, the ethyl acetate (EA), n-hexane (HE), methylene chloride (MC), n-butanol (BU) fractions of the leaves of S. buxifolia were screened for the in vitro antiprotozoal activity against Plasmodium falciparum, Trypanosoma brucei, Trypanosoma cruzi and Leishmania infantum. Hexane and MC fractions showed good antiprozoal activity (IC50 for HE8.56, 8.64, 3.37, 10.26 µg/mL and MC 8.20, 12.7, 32.69, 2.63 µg/mL) against T. cruzi, L. infantum,T. brucei,and P. falciparum respectively. However, the EA and BU were inactive. Accordingly, two major compounds were isolated from HE identified as and friedelin (1) and β-sitosterol (2) while two coumarins were isolated from MC and identified as seselin (3) and (+)-ulopterol (4). Identification of the compounds was carried out based on mass spectrometry, proton and carbon 1D NMR, as well as 1H-13C HSQC and HMBC spectral analysis. Among isolated compounds, only seselin showed antiprotozoal activity with IC50 of 38.47 and 38.5 mg/mL against T. cruzi and P. falciparum, respectively and no cytotoxicity. Furthermore, an HPLC fingerprint for each fraction was achieved with the aim of authenticating the plant chemical profile and identified seslin and ulopterol as major constituents of the plant extract.